The Fine Tuning of Drp1-Dependent Mitochondrial Remodeling and Autophagy Controls Neuronal Differentiation - Vantaggiato, Chiara; Castelli, Marianna; Giovarelli, Matteo; Orso, Genny; Bassi, Maria Teresa; Clementi, Emilio; De Palma, Clara (Frontiers in Cellular Neuroscience, 2019)
Mitochondria play a critical role in neuronal function and neurodegenerative disorders, including Alzheimer’s, Parkinson’s and Huntington diseases and amyotrophic lateral sclerosis, that show mitochondrial dysfunctions associated with excessive fission and increased levels of the fission protein dynamin-related protein 1 (Drp1). Our data demonstrate that Drp1 regulates the transcriptional program induced by retinoic acid (RA), leading to neuronal differentiation. When Drp1 was overexpressed, mitochondria underwent remodeling but failed to elongate and this enhanced autophagy and apoptosis. When Drp1 was blocked during differentiation by overexpressing the dominant negative form or was silenced, mitochondria maintained the same elongated shape, without remodeling and this increased cell death. The enhanced apoptosis, observed with both fragmented or elongated mitochondria, was associated with increased induction of unfolded protein response (UPR) and ER-associated degradation (ERAD) processes that finally affect neuronal differentiation. These findings suggest that physiological fission and mitochondrial remodeling, associated with early autophagy induction are essential for neuronal differentiation. We thus reveal the importance of mitochondrial changes to generate viable neurons and highlight that, rather than multiple parallel events, mitochondrial changes, autophagy and apoptosis proceed in a stepwise fashion during neuronal differentiation affecting the nuclear transcriptional program.